Audit Markets in Russia and China - Yali Liu (Учёт. Анализ. Аудит)
This research describes and analyzes the auditing markets of two world powers, such as Russia and China. Russia has studied the concept of the development of auditing activities. This concept assumes the formation of a system for the development of the audit services market in Russia, which has unrealized opportunities for its improvement, considering modern realities. The article considers the current state of affairs in the industry, the existing legal framework, analyzes the role of the state in the market’s development for audit services in the country. The paper also presents the postulates of auditing in China, whose standards are closest to international norms and guidelines in several important aspects. In addition, China has developed a state audit using an executive regime. As a result of the study, the author revealed the relationship between the audit index and the fact of corruption, and proposed possible key directions for the development of the audit markets in Russia and China. Since audit is becoming an important area of world activity, contributing to the development of the economy, the purpose of this study is to identify the features of the development of the audit markets in Russia and China, its object is the audit market, and the subject is audit activities in these countries.